Oral plasmablastic lymphoma: A clinicopathological study of 113 cases. (1st July 2021) - Fonseca, Felipe Paiva; Robinson, Liam; van Heerden, Marlene B.; van Heerden, Willie F. P.
Abstract: Background: Plasmablastic lymphoma (PBL) is an aggressive neoplasm that commonly develops in HIV‐positive patients, usually affecting the oral cavity. EBV is present in the majority of cases, therefore, playing an important role in the pathogenesis of this neoplasm. Methods: PBL diagnosed from 2000 to 2020 were retrieved from the archives of the Department of Oral Pathology and Oral Biology at the University of Pretoria, South Africa. The patients' clinical information including gender, age, tumour location and HIV status was obtained from the original histopathology request forms. A morphological description was assessed using H&E‐stained slides, with diagnoses confirmed by immunohistochemistry, and EBV detection performed via in situ hybridisation. Results: During the 20 years period investigated, 113 PBL were found. Males outnumbered females (M:F ratio of 3:1), with a median age of 41 years (range 8–62). The gingiva (50 cases or 44.2%) and the palate (23 cases or 20.4%) were the most affected sites. All cases with available information were HIV positive. The tumours were composed of a diffuse proliferation of immunoblasts or plasmablasts in all cases. A starry‐sky pattern, tissue necrosis, cellular pleomorphism and mitotic figures were common microscopic findings. IHC for CD3 and CD20 were negative in all cases, while positivity for CD38, CD138 and MUM1 was observed in 70.2%, 79.2% and 98.9%, respectively. EBV was present in 100% of the cases. Conclusion: PBL is a frequent diagnosis in South Africa, due to the country's HIV burden, where it usually affects the oral cavity and is always associated with EBV infection.